Analisis Resepsi Kekerasan Seksual pada Perempuan dalam Film Penyalin Cahaya - Netanya Astu P.D., Raden Roro; Kusuma, Satria (Jurnal InterAct, 2023)
The film “Penyalin Cahaya” is a film that addresses the issue of sexual violence against women. Sexual violence in Indonesia still occurs frequently, both verbally and non-verbally. The film "Penyalin Cahaya"tells the story of the sexual violence and harassment experienced by Suryani and Farah, committed by Rama, a member of Theater Matahari. The purpose of this research is to understand the interpretation of sexual violence against women in the film“Penyalin Cahaya.” The theories used in this research are reception analysis and sexual violence. This research employs a qualitative descriptive research method and uses Stuart Hall’s reception analysis. Data collection techniques include in-depth interviews with twelve informants and literature reviews. The results of this research explain that eight informants are categorized as dominant-hegemonic, and four informants fall into a negotiated position, but there are no informants categorized as opposition positional. According to the informants, the film “Penyalin Cahaya” is effective in representing the issue of sexual violence against women, although some informants find the plot and ending of the film not easily understandable.